Enhancing Performance of Health Assistants through Technical and Vocational Education and Training for Better Healthcare Access - Basnet, Rojina; Karki Pyakurel, Chetan (Journal of Technical and Vocational Education and Training, 2024)
This is a review article exploring critical role of Technical and Vocational Education and Training (TVET) programs in advancing capacities of health assistants and consequently strengthening healthcare access to the rural population in Nepal. The review was planned in the wake of the existing literatures on the study area that lacks a comprehensive examination to explores the role of health assistants in Nepal's healthcare delivery and assess the importance of TVET on their performance. A methodical literature search was conducted using various electronic databases like Google scholar and PubMed applying specific keywords, such as “Health Assistant", "Health Care Access", "Technical Education", "Vocational Education and Training”. It encompassed the studies published in the English language without limiting publication date, while the involved two authors independently evaluated the published articles' eligibility. These authors also carried out data extraction, culminating in a narrative summary of the findings. Of the total 37 literatures, most of them reported health assistant trained through TVET, play a vital role in improvement of healthcare access, thereby addressing the challenges. They bridge gaps in medical access, provide essential care, and promote community well-being, particularly in the underserved areas. TVET programs enhance skills through practical experiences and comprehensive training, resulting into significant improvement in healthcare access, especially in rural regions. Integrating innovative teaching methods and collaborations further enhances health assistant preparedness. Challenges, such as funding limitations and rural-urban divides persist, but opportunities exist in e-learning initiatives, partnerships, and professional development to improve health assistant education. Improving healthcare in Nepal by inculcating better skills to health assistants can address many healthcare problems.